Demographic & related differences in ethical views among small businesses - Serwinek, Paul J. (Journal of business ethics, 1992)
This study examines the effects of demographic characteristics on ethical perceptions. While earlier research has produced conflicting results regarding the predictive power of these variables, significant and definite insights were obtained with proper controls. The following predictors of ethical attitudes are examined: age, gender, marital status, education, dependent children status, region of the country and years in business, while controlling for job status. A nation-wide random sample of employees was used in obtaining a response rate of fifty-three percent (total n of 423). Indices of aspects of business ethical attitudes were constructed using factor analysis. Linear multiple regression analysis indicated the significant predictive variables. Age was found to be a most-significant predictor. Older workers had stricter interpretations of ethical standards. Gender and region predicted attitudes about job-discrimination practices only, with women and persons from the Midwest most strongly opposed to the practice. All the other variables proved to be unreliable ethics predictors.